Development of Pop-UP Book Learning Media on Ecosystem Topics in Elementary School Science Learning - Erika Amelia Triyana; Aan Yuliyanto; Neng Wuilan Evi Juliani; Bunayah; Ade Sumini; Nur Afifah Tussholihati (International Conference on Elementary Education, 2023)
Learning media is a tool that contains information on a learning topic that can attract the attention and interest of students in following the learning process in class and achieving learning objectives. This research is motivated to increase enthusiasm and enthusiasm in learning science on the topic of elementary school ecosystems so that students can understand the importance of maintaining the balance of the ecosystem and achieving learning objectives. This research aims to develop and produce a pop-up book learning media to assist students in understanding the topic of ecosystem learning. This research was conducted by the R&D method. The initial stages in making a pop-up book are determining the storyline, designing images, printing images, and cutting images, and the last is making a slide pop-up book and pasting the cut-out images into the slide pop-up book. By using the pop-up book learning media, students are expected to understand the concept of an ecosystem. This living environment interacts and depends on each other, consisting of biotic elements consisting of living and abiotic creatures consisting of inanimate objects such as the sun, concretely and effectively.